Administração intravenosa de emulsão lipídica de isofluorano em cães - Almeida, Ricardo Miyasaka de [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
A administração intravenosa de anestésicos voláteis halogenados pode ser considerada uma alternativa à aplicação pela via inalatória, e neste contexto, as formulações emulsificadas têm mostrado segurança, eficiência e bons planos anestésicos. Neste estudo, objetivou-se comparar os efeitos hemodinâmicos e respiratórios das administrações intravenosa e inalatória de isofluorano em cães, após a determinação da taxa de infusão intravenosa de 6,99 mL/kg/h deste halogenado em emulsão lipídica. Para tanto, foram utilizados oito cães, os quais formaram três grupos distintos: grupo IV – anestesia intravenosa por infusão de emulsão lipídica com isofluorano; grupo E - anestesia inalatória com isofluorano, associada à infusão intravenosa de emulsão lipídica sem o halogenado; e grupo IN - anestesia inalatória com isofluorano, associada à infusão intravenosa de solução de NaCl 0,9%. Foram evidenciadas diminuições da contratilidade cardíaca, índice cardíaco e pressão arterial sistêmica a partir de 10 e 40 minutos de anestesia, respectivamente, nos grupos IV e E. A hipotensão no grupo IV resultou em acidose metabólica, porém, hipoxemia não foi observada. O grupo IN apresentou manutenção do índice cardíaco, apesar de reduções do índice de resistência vascular sistêmica e pressão arterial. A taxa de infusão intravenosa determinada foi efetiva na manutenção de plano de anestesia cirúrgica em cães. As infusões intravenosas de isofluorano e emulsão lipídica causaram depressão cardíaca e hipotensão. Em relação à função respiratória, nenhum dos grupos mostrou efeitos deletérios.

The intravenous administration of halogenated anesthetics can be considered an alternative to the application by the inhalation route, moreover, emulsified formulations have been showing safety, efficiency and appropriated anesthetic depth. The aim of this study was to compare the effects of isoflurane anesthesia by intravenous or inhalational route on hemodynamic and respiratory variables, after the determination of the intravenous infusion rate of 6.99 mL/kg/h of this anesthetic in lipid emulsion, in dogs. Therefore, eight dogs were distributed in three different protocols: IV group – intravenous anesthesia with emulsified isoflurane; E group – inhalational anesthesia with isoflurane associated to intravenous infusion of lipid emulsion; and IN group - inhalational anesthesia with isoflurane associated to intravenous infusion of 0.9% NaCl solution. The results regarding IV and EM groups revealed decreases of heart contractility, cardiac index and systemic blood pressure starting from 10 and 40 minutes of anesthesia, respectively. The hypotension in the IV group resulted in metabolic acidosis, however, hypoxemia was not observed. The IN group demonstrated maintenance of cardiac index, despite of reduction of the blood pressure and systemic vascular resistance index. The intravenous infusion rate determined was effective in the maintenance of an anesthetic depth of general anesthesia in dogs. The intravenous infusions of isoflurane and lipid emulsion caused cardiac depression and hypotension. In relation to respiratory function, the inhalational route and the intravenous infusions of isoflurane and lipid emulsion did not result in harmful effects.
Keywords: Cão; Anestesia veterinaria; Anestesia geral inalatória; Anestesia total intravenosa; Emulsão lipídica; Isofluorano; Dog; Inhalation anesthesia; Intravenous anesthesia; Lipid emulsion; Emulsified isoflurane